A Review on Atibhakshana Chikitsa and Virudha Ahara in Ayurveda, Specifically from Prayoga Samucchaya - Alex, Littija; Ravishankar , K; Bharath, Ashwini Kumar S (International Research Journal of Ayurveda & Yoga, 2023)
Since the time of the Vedic civilization, Ahara has been regarded as a precious gem. Ahara is first among the three significant pillers of ayurveda. Ayurveda gives highest importance to maintenance of health and to promote positive health which can be attained through ahara. When consumed in proper way food maintains the body while ati(excess), mithya(improper), hinayoga(inadequate manner) leads to harmful effects on body. Matravat Ahara (equivalent quantity of food) aids in bringing happiness & longevity to the person without upsetting the balance of Doshas & Dhatus. The daily routine and eating habits have significantly changed in the modern period. Our bodies are exposed to numerous toxins as a result of these radical changes in lifestyle and eating habits. Prayoga Samucchayam is most well known and often used books in Agada Tanta (toxicology), which is one among the 8 branches of Ayurveda. It elaborately explains Athibhakshana (over eating) chikitsa and virudha bhakshana (incompatible food) and also offers a selection of simple treatment remedies that are quick to make and can be used to treat various illnesses. It places a strong focus on the need of understanding the concept of ahara and how to live a healthy existence. If one comprehends this core idea, even a layperson in an emergency circumstance without access to a doctor or nearby medical care can administer these easily accessible medications at home as a first aid treatment.